Eight-year outcomes of a competency-based residency training program in orthopedic surgery. (3rd October 2018) - Nousiainen, Markku T.; Mironova, Polina; Hynes, Melissa; Glover Takahashi, Susan; Reznick, Richard; Kraemer, William; Alman, Benjamin; Ferguson, Peter; ,
Abstract: Background: The Division of Orthopaedic Surgery at the University of Toronto implemented a pilot residency training program that used a competency-based framework in July of 2009. The competency-based curriculum (CBC) deployed an innovative, modularized approach that dramatically intensified both the structured learning elements and the assessment processes. Methods: This paper discusses the initial curriculum design of the CBC pilot program; the refinement of the curriculum using curriculum mapping that allowed for efficiencies in educational delivery; details of evaluating resident competence; feedback from external reviews by accrediting bodies; and trainee and program outcomes for the first eight years of the program's implementation. Results: Feedback from the residents, the faculty, and the postgraduate residency training accreditation bodies on the CBC has been positive and suggests that the essential framework of the program may provide a valuable tool to other programs that are contemplating embarking on transition to competency-based education. Conclusions: While the goal of the program was not to shorten training per se, efficiencies gained through a modular, competency-based program have resulted in shortened time to completion of residency training for some learners.